Quantifying Channel Mobility and Floodplain Reworking Timescales Across River Planform Morphologies - Evan Greenberg; Austin J. Chadwick; Gen K. Li; Vamsi Ganti (Geophysical Research Letters, 2024)
Abstract Source‐to‐sink transfer of sediment and organic carbon (OC) is regulated by river mobility. Quantifying trends in river mobility is, however, challenging due to diverse planform morphologies (e.g., meandering, braided) and measurement methods. Here, we utilize a remote‐sensing method applicable to all planform morphologies to quantify the mobility timescales of 80 rivers worldwide. Results show that, across the continuum from meandering to braided rivers, there is a systematic reduction in the timescales of channel mobility and—to a lesser extent—floodplain reworking. This leads to a decrease in the efficiency with which braided rivers rework old floodplain material compared to their meandering counterparts. Reduced floodplain reworking efficiency of braided rivers leads to smaller channel‐belt areas relative to their size. Results suggest that river‐mobility timescales derived from remote sensing can aid in the characterization of sediment and OC storage and transit times at a global scale.